Assessment the socio-economic drought vulnerability index in the Red River delta - Lan, Vu Thi Thu; Vinh, Lai Tien; Son, Hoang Thanh (Vietnam Journal of Earth Sciences, 2015)
During recent years, the situation of drought, lack of water for developing   economy have been an increasing. In order to cope efficiently with drought disaster, it is necessary to determine ability of economy when it has to confront the lack of water. Depending on economic structures of the Red River Delta , it is first time, this report apply socio-economic drought vulnerability index (SDI) to evaluate sensitive levels of economy on the drought and lack of water. Analyzing the indexes rely on consider that it contributes higher into gross domestic product (GDP) from non-agriculture area and lower percentage on agriculture labors as well as diversified crop plants. On the basis of city/provincial statistical data, in continuous 13 years (from 2000 to 2012), it has been determined the sensitive drought indexes (SDI) for each city/province and the whole area. The results of SDI in the Red River Delta in the period of 2000 - 2013 have reflected transfer of the economic structure as well as the economic growth rate of the area, the SDI in the Red River Delta is directly proportional to density of agriculture branch for the gross domestic product (GDP) and it shows the real situation of sensitive level of agriculture branch when it happens drought and lack of water. The index is frame tool for “drought total management” and scientific principles in order to adjust suitability for using water resources toward the drought total management, making suitable strategy proposals including land management policy and national resources.ReferencesNguyễn Lập Dân, 2010: Nghiên cứu cơ sở khoa học quản lý hạn hán và sa mạc hóa để xây dựng hệ thống quản lý, đề xuất các giải pháp chiến lược và tổng thể giảm thiểu tác hại: nghiên cứu điển hình cho ĐBSH và Nam Trung Bộ. Báo cáo tổng kết đê tài KHCN trọng điểm cấp Nhà nước, KC 08-23/06-10, lưu trữ tại Cục thông tin khoa học và công nghệ quốc gia, Bộ KH&CN, Hà Nội. Nguyễn Văn Dân, 2010: Nghiên cứu giải pháp đảm bảo cấp nước mùa kiệt các hệ thống thủy lợi ĐBSH. Báo cáo tổng kết đề tài. Lưu trữ Bộ NN&PTNT. Jülich, S. 2006: Drought risk indicators for assessing rural households. Presentation made at Global Water Hotspots: Water-related social vulnerabilities and resilience-building, Summer Academy for Social. Vũ Thị Thu Lan, Hoàng Thanh Sơn, 2013: Thực trạng và nguyên nhân thiếu nước vùng ĐBSH, Tạp chí Các Khoa học về Trái Đất 4, T.35, (4), tr.374-380. Vũ Thị Thu Lan, Đỗ Minh Phương, Lê Nhị Thủy, Lại Tiến Vinh, 2014: Xác định hạn hán vùng ĐBSH qua chỉ số mức độ khô hạn nhiệt độ - thực vật (TDVI), Tạp chí Khoa học và Công nghệ 19, 40, Hà Nội. Nishadi Eriyagama, 2010: Mapping Drought Patterns and Impacts: A Global Perspective, IWMI Research Report 133, International Water Management Institute P O Box 2075, Colombo, Sri Lanka. Nguyễn Văn Thắng, 2015: Nghiên cứu và xây dựng công nghệ dự báo và cảnh báo sớm hạn hán ở Việt Nam. Báo cáo tổng kết Đề tài KHCN cấp Nhà nước KC08-17/11-15. Lưu trữ tại Cục thông tin khoa học và công nghệ quốc gia, Bộ KH&CN, Hà Nội. Trần Thục, Koos Neefjes, 2015: Báo cáo đặc biệt của Việt Nam về quản lý rủi ro thiên tai và các hiện tượng cực đoan nhằm thúc đẩy thích ứng với biến đổi khí hậu, Nxb. Tài nguyên - Môi trường và Bản đồ Việt Nam, Hà Nội (451 trang). Tổng cục thống kê, Niên giám thống kê của 10 tỉnh, thành phố thuộc ĐBSH (Tp. Hà Nội, Tp. Hải Phòng, Vĩnh Yên, Bắc Ninh, Hải Dương, Hưng Yên, Hà Nam, Nam Định, Thái Bình, Ninh Bình) từ năm 2000 đến năm 2012. UNDP, 2012: Báo cáo phát triển con người năm 2012 của Liên Hiệp Quốc.